Short-Time Work and Precautionary Savings - Thomas Dengler; Britta Gehrke (Center for Economic Studies and ifo Institute (CESifo), 2022)
In the Covid-19 crisis, most OECD countries have used short-time work (subsidized working time reductions) to preserve employment relationships. This paper studies whether short-time work can save jobs through stabilizing aggregate demand in recessions. First, we show that the consumption risk of short-time work is considerably smaller compared to unemployment using household survey data from Germany. Second, we build a New Keynesian model with incomplete asset markets and labor market frictions featuring an endogenous firing and short-time work decision. In recessions, short-time work reduces the unemployment risk of workers, which mitigates their precautionary savings motive. Using a quantitative model analysis, we show that this channel increases the stabilization potential of short-time work over the business cycle.
Keywords: E21; E24; E32; E52; E62; J63; 330; short-time work; fiscal policy; incomplete asset markets; unemployment risk; matching frictions